Incidencia de las reformas tributarias del impuesto a la renta en la empresa Rosas del Corazón cía. ltda., en los años 2019 y 2020 - López Cevallos, Rosa Amanda (2023)
The objective of this research work is to determine the incidence of the tax reforms presented in the liquidation and payment of income tax in the company Rosas del Corazón Cía. Ltda., in the years 2019 and 2020, for which the Tax Conciliation was carried out in order to improve the application of the regulations set forth in the corresponding years, as well as the recognition and calculation of deductible and non-deductible expenses with due justification. A quantitative method was applied to analyze the information obtained from the company through research tools such as the interview used with accounting area personnel.